Continuous “Morphing”: Competing Through Dynamic Capabilities, Form, and Function - Rindova, Viólina; Kotha, Suresh (Academy of Management Journal, 2001)
In hypercompetitive environments, the established paradigms of sustainability of competitive advantage and stability of organizational form may have limited applicability. Using an in-depth case analysis of the firms Yahoo! and Excite, this study examines how the organizational form, function, and competitive advantage of these firms dynamically coevolved. The study introduces the concept of continuous morphing to describe the comprehensive ongoing transformation through which the focal firms sought to regenerate their transient competitive advantage on the Internet.